Killings - Trillin, Calvin (Random House, 2017)
"Reporters love murders," Calvin Trillin writes in the introduction to Killings. "In a pinch, what the lawyers call "wrongful death" will do, particularly if it's sudden." Killings, first published in 1984 and expanded for this edition, shows Trillin to be such a reporter, drawn time after time to tales of sudden death. But Trillin is attracted less by violence or police procedure than by the way the fabric of people's lives is suddenly exposed when someone comes to an untimely end"--Amazon.com.